How do you solve the quadratic using the quadratic formula given #3a^2=6a-3#?

1 Answer
Jan 17, 2017

Answer:

#a=1#

Explanation:

Rearrange:
#3a^2-6a+3=0#

Use the formula #a=(-b+-sqrt(b^2-4ac))/(2a)# taking care not to get the #a#'s muddled

Formula Problem
a 3
b -6
c 3
x a

#a=(-(-6)+-sqrt((-6)^2-4 xx 3 xx 3))/(2 xx 3)#
#a=(6+-0)/(2 xx 3)#
#a=1# (repeated root).

Check: #3xx(1)^2=3# and #6xx(1)-3=3#

If you get muddled over the #a#'s just replace all the #a#'s with #x#'s, apply the formula, then at the step replace the #x# with #a#.